Analysis of Workforce Planning Strategies to Improve Operational Efficiency at FreeStyle Jacket Manufacturing - Resya Dwi Marselina; Devan Gilang Ramadhan; Najwa Silva Indrianti; Rianty Reztu Suryadi; Ryani Viayu; Salwa Anisyahara Gunawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Workforce planning plays a critical role in supporting operational efficiency and organizational sustainability within labor intensive manufacturing industries. This study aims to analyze workforce planning strategies implemented at FreeStyle Jacket Manufacturing and examine their contribution to operational efficiency within a decentralized make to order production system. The research employed a qualitative descriptive approach using an empirical research design. Data were collected through in depth interviews, direct observations, and analysis of company documents involving managerial personnel and production partners. The findings reveal that workforce planning practices are primarily characterized by labor retention efforts, competency based workforce development, operational flexibility, and production coordination across partner workshops. These practices contribute to maintaining production continuity, quality consistency, and resource utilization despite challenges related to fluctuating demand and geographically dispersed production units. The study also identifies limitations associated with intuition based decision making, including the absence of workforce forecasting, workforce analytics, and integrated labor information systems. Strategic analysis suggests that future improvements require the adoption of data driven workforce planning supported by digital technologies, predictive workforce management, and sustainable human resource development to strengthen long term operational performance and organizational adaptability.